The Use of Dietary Supplements and Medications by Canadian Athletes at the Atlanta and Sydney Olympic Garnes - Huang, S. H.; Johnson, K.; Pipe, A. (Clinical Journal of Sport Medicine, 2006)
Objective: To learn more about the prevalence of dietary supplement and medication use by Canadian athletes in the Olympic Games in Atlanta 1996 and Sydney 2000.